2009
DOI: 10.1002/dmrr.1056
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKCζ translocation in the development of type 2 diabetes in rats following continuous glucose infusion

Abstract: Translocation of PKCzeta may play a central role in the development of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
6
0
2
Order By: Relevance
“…insulin-like growth factor-1 receptors and TrkB receptors) and other receptors involved in memory formation may regulate GluT4 [91][92][93][94] . Downstream of receptor activation, GluT4 translocation is regulated by several post-receptor signaling molecules critical for maintaining long term memory including insulin-like growth factor 2, brain-derived neurotrophic factor, Ca 2+ /calmodulindependent protein kinase II, phosphoinositide 3-kinase (PI3K), protein kinase A, MAPK, protein kinase-λ, and -protein kinase-ζ [91][92][93][94][95][96][97][98][99][100][101] . Some non-receptor activation-dependent conditions are associated with GluT4 trafficking and activity, such as cellular depolarization via elevated intracellular [Ca 2+ ] and elevated extracellular [K + ] 102-106 ; as noted below, this includes recruitment of GluT4 to the synapse as a consequence of neuronal activity 107 , a seminal recent finding that is consistent with prior work showing increased cerebellar GluT4 after prolonged exercise 108 .…”
Section: Mechanisms By Which Insulin Enhances Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…insulin-like growth factor-1 receptors and TrkB receptors) and other receptors involved in memory formation may regulate GluT4 [91][92][93][94] . Downstream of receptor activation, GluT4 translocation is regulated by several post-receptor signaling molecules critical for maintaining long term memory including insulin-like growth factor 2, brain-derived neurotrophic factor, Ca 2+ /calmodulindependent protein kinase II, phosphoinositide 3-kinase (PI3K), protein kinase A, MAPK, protein kinase-λ, and -protein kinase-ζ [91][92][93][94][95][96][97][98][99][100][101] . Some non-receptor activation-dependent conditions are associated with GluT4 trafficking and activity, such as cellular depolarization via elevated intracellular [Ca 2+ ] and elevated extracellular [K + ] 102-106 ; as noted below, this includes recruitment of GluT4 to the synapse as a consequence of neuronal activity 107 , a seminal recent finding that is consistent with prior work showing increased cerebellar GluT4 after prolonged exercise 108 .…”
Section: Mechanisms By Which Insulin Enhances Memorymentioning
confidence: 99%
“…CaMKII, DHA, PKC, PKA, BDNF, cellular depolarization, etc.) regulate GluT4 in adipocytes and muscle [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] . It will be important to determine which of these effects also occur in neurons.…”
Section: Peripheral Vs Central Regulation Of Glut4mentioning
confidence: 99%
See 1 more Smart Citation
“…Further understanding of the central role of caveolins in cardiac and insulin signaling under normal conditions will facilitate discovery of new treatment approaches for DCM. In insulin signaling cascades, phosphatidylinositol 3-kinase (PI3K) activates the major downstream effector Akt kinase, also termed protein kinase B (PKB), which modulates glucose uptake by facilitating GLUT4 translocation ( 136 ). Short-term exposure of mature adipocytes to glucose reduces Cav-1 expression and insulin sensitivity, but during adipocyte differentiation, chronic exposure to high glucose triggers adaptive response by adipocytes, manifested by increased protein expression of Cav-1, IR, and Akt ( 137 , 138 ).…”
Section: Caveolin and Its Potential As A Treatment Target For Diabeti...mentioning
confidence: 99%
“…One study found that PI3K subunit p85 transferred from cytosol to the cytomembrane within one minute under 10 −7 mol/L insulin stimulus in rat fibroblasts in which insulin receptor (IR) was highly expressed, while PKC ζ transferred from cytosol to the cytomembrane within one to 10 minutes [ 10 ], which suggested that PI3K activation occurred prior to PKC ζ, and PI3K may regulate PKC ζ directly in the cytomembrane. In a resting state, inactive PKC ζ locates in the cytoplasm, while it translocates to the cell membrane and becomes active upon stimulus [ 11 ]. However, how PKC ζ translocates from cytosol to the cytomembrane remains unclear.…”
Section: Introductionmentioning
confidence: 99%